Synergistic impact of Serendipita indica and Zhihengliuella sp. ISTPL4 on the mitigation of arsenic stress in rice - Sharma, Neha; Yadav, Gaurav; Tyagi, Jaagriti; Kumar, Ajay; Koul, Monika; Joshi, Naveen Chandra; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Mishra, Arti (Frontiers in Microbiology, 2024)
Arsenic (As) is a highly toxic metal that interferes with plant growth and disrupts various biochemical, and molecular processes in plants. In this study, the harmful effects of As in rice were mitigated using combined inoculation of a root endophyte Serendipita indica and, an actinobacterium Zhihengliuella sp. ISTPL4. A randomized experiment was conducted, in which rice plants were grown under controlled conditions and As stressed conditions. The control and treatment groups consisted of untreated and non-stressed plants (C1), treated and non-stressed plants (C2), stressed and untreated plants (T1), and stressed and treated plants (T2). Various phenotypic characteristics like shoot length (SL), root length (RL), Shoot fresh weight (SFW), Root fresh weight (RFW), Shoot dry weight (SDW), and Root dry weight (RDW)) and, biochemical parameters like chlorophyll content, protein content and antioxidant enzymatic activities were evaluated. The activity of various antioxidant enzymes was increased in T2 followed by T1 plants. Furthermore, high concentrations of phytohormones like Ethylene (ET), Gibberellins (GA), and Cytokinin (CK) were found at 4.11 µmol mg -1 , 2.53 µmol mg -1 , and 3.62 µmol mg -1 of FW of plant respectively. Results of AAS indicated an increased As accumulation in roots of T2 plants (131.5 mg kg -1 ) than in roots of T1 plants (120 mg kg -1 ). It showed that there was an increased As accumulation and sequestration in roots of microbialtreated plants (T2) than in uninoculated plants (T1). Our data suggest that this microbial combination can be used to reduce the toxic effects of As in plants by increasing the activity of antioxidant enzymes like SOD, CAT, PAL, PPO and POD. Furthermore, rice plants can withstand As stress owing to the active synthesis of phytohormones in the presence of microbial combinations.